1992
DOI: 10.1128/aem.58.12.3834-3836.1992
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Ag+ for preservative use

Abstract: In contact experiments with different experimental conditions, electrochemical Ag+ solutions exhibited better antimicrobial effectiveness against bacteria, a yeast species, and a mold than did analogous silver solutions from inorganic salts. The particular characteristics of electrochemical Ag+, such as the mode of action, effectiveness at low concentrations, and stability, indicate that Ag+ could be used effectively in preservatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 6 publications
0
28
0
1
Order By: Relevance
“…In a recent paper, the antimicrobial activities /of AgN03, AgCl and Ag ions obtained through electrochemipal methods were compared. We demonstrated that anodic silver ions showed highest activity also when challenged with large inocula (Simonetti et al 1992). This rnicrobicidal activity appeared particularly enhanced at higher temperatures.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…In a recent paper, the antimicrobial activities /of AgN03, AgCl and Ag ions obtained through electrochemipal methods were compared. We demonstrated that anodic silver ions showed highest activity also when challenged with large inocula (Simonetti et al 1992). This rnicrobicidal activity appeared particularly enhanced at higher temperatures.…”
mentioning
confidence: 67%
“…Electrochemical silver solutions were prepared using a 4.5-V battery connected to two cylindrical silver electrodes (length, 8 cm; cross section, 4 mm'; distance between electrodes, 3cm) in a 100-mL glass cylinder. In all samples, the Ag+ concentration was determined, as previously reported (Simonetti et al 1992), by a potentiometric method using an Ag,S electrode. Silver ion concentration was adjusted to M in each experiment.…”
Section: Methodsmentioning
confidence: 99%
“…12 Ag nitrated coatings have also been studied for years because Ag ion is known to exhibit antibacterial properties. 13 Stainless steel pins coated with Ag have been found to decrease the adhesion and colonization of S. aureus, Staphylococcus epidermidis, and P. aeruginosa around the coated implant. 14,15 However, there are also reports that Ag is toxic to host cells, causing severe toxic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…8 -10 Colloidal silver is a completely nontoxic, tasteless, internally and externally applicable, broad-spectrum germ fighter and disinfectant, which can significantly reduce the length and severity of many bacterial infections. [11][12][13] Silver is used as coating 14,15 and also as particulate filler 16,17 in various polymers to generate antimicrobial property. Many commercial fillers (containing silver) available in the markets rely on certain carrier materials, such as titanium dioxide, sodium hydrogen zirconium phosphate, or some zeolite, as carriers of silver whose presence will improve the water permeability of the composite specimen.…”
Section: Introductionmentioning
confidence: 99%